Concepções sobre o AEE e o trabalho pedagógico realizado com estudantes com autismo: dilemas e possibilidades - Scuzatto, Adeliana das Gracas Lima (2023)
The presented research aims to develop a study on the conceptions of professionals who work in the Specialized Educational Assistance (AEE) in Multifunctional Resource Room (SRM), about their pedagogical practices experienced with students with autism. In order to understand the questions proposed in the study, the research was developed with teachers hired by temporary assignment (DT) who work in resource rooms in the municipal educational system of Nova Venécia/ES. The choice to include in the participant group of research teachers who work under the hiring regime by temporary assignment is justified by the issue of the annual turnover of these teachers and the need for pedagogical training in working with Special Education students, specifically students with autism. The study is theoretically and methodologically based on the historical-cultural approach of human development processes and on historical-dialectical materialism, postulated by Vigotski (1997) and his collaborators, passing through the readings of their studies on defectology in terms of learning processes and development of people with disabilities. The research proposition included monthly, face-to-face meetings, using the focus group technique, because this one allows the analysis of results, the elaboration of strategies, plans and the production of new ideas. In that regard, it is relevant to think about the work of the Special Education teacher who provides specialized educational services in the resource room. In the AEE that takes place in SRM, howdoes the teacher in charge prepare or is prepared to answer the demands of the public that attends this space, more specifically the student with autism? During the dialogues, discussions and reflections, the teachers realized that the SRM makes up the whole of the school, that the attributions of the teachers who work there extend to the common room, that it is necessary to know who the student is, that their life story is part of their learning process and is present in their development. The difficulties listed were several, however, very common to all in the school environment. In the last meeting of the focus group, the teachers' testimonies showed how much we have grown and matured with the exchange of experiences and with the shared readings.